(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Effect of Demand, Substitute Goods and Availability of Cayenne Pepper on Sales (Case Study on Traders in Badung Traditional Market, West Denpasar District, Denpasar City). Badung Traditional Market is located in West Denpasar District, Denpasar City. The largest Traditional Market in Bali is a place that is visited by many domestic and foreign tourists and has the largest number of traders in the city of Denpasar, one of which is cayenne pepper traders who are able to create diversity in the price of cayenne pepper in each trader with one another so that it affects the sale of cayenne pepper in Badung Traditional Market. This study aims to analyze the effect of demand, substitute goods and the availability of cayenne pepper in traders on the sale of cayenne pepper in Badung Traditional Market. This study uses primary data and secondary data. To achieve these objectives, the analytical method used in this study is multiple linear regression analysis with the IBM SPSS 26 program. The results showed that the results of the classical assumption test obtained were met and met the requirements of the linear regression model and it was known that the data for the demand variable obtained Thitung 3.478> 2.048 and the significance value was 0.002 <0.05, which means that it has an effect on the sale of cayenne pepper in Badung Traditional Market, while the substitute goods variable obtained Thitung -0, 958> 2.048 and its significance value is 0.346> 0.05 which means it has no effect on the sale of cayenne pepper in Badung Traditional Market and the variable availability of cayenne pepper in traders obtained Thitung 8.567> 2.048 and its significance value is 0.000<0.05 which means it has an effect on the sale of cayenne pepper in Badung Traditional Market. It is known that simultaneously the independent variables (demand, substitute goods and availability of cayenne pepper in traders) as a whole have a significant effect on the sale of cayenne pepper in Badung Traditional Market.